Current Knowledge of Breastfeeding Among Health Workers in a Developing Country Setting: A Survey in Calabar, Nigeria - Ikobah, Joanah M (Cureus, 2020)
Background Health workers are in a strategic position to provide correct information to mothers on breastfeeding practice. This study assessed knowledge of breastfeeding among health workers in health facilities in Calabar. Methods This was a cross-sectional descriptive study. A 45-item self-administered questionnaire was used to obtain data. Ethical clearance for the study was obtained from the Cross River State Research and Ethics Committee. Data were analyzed using SPSS version 21.0 (SPSS, Inc., Chicago, USA). A knowledge score of at least 90% was considered satisfactory. Factors associated with the level of knowledge were determined using chi-square. The p-value was set at 0.05. Result Two hundred and twenty-five healthcare professionals were surveyed, with a mean age of 37.5 ± 9.4 years, ranging from 20 to 65 years. The commonest age group was 41 to 50 years (43.1%). Females (80.9%) formed a larger proportion of participants with a female-male ratio of 4:1. The mean percentage of knowledge score was 85.1 ± 9.0%. A satisfactory level of knowledge was found in 27.1% of respondents. About one-third (33.7%) and one-fifth (21.8%) of health workers were not aware of the weight control benefit and protection against osteoporosis of breastmilk, respectively. Approximately one-fifth (22.2%) of respondents had misconceptions concerning the effects of colostrum on the prevention of neonatal jaundice. Nurses with diploma level of training had a satisfactory level of knowledge, compared with other professions (p < 0.05). Conclusion Health workers’ knowledge of breastfeeding was generally good though suboptimal. Health-related professions should provide current information on the best breastfeeding practices.